2008
DOI: 10.1158/0008-5472.can-08-0247
|View full text |Cite
|
Sign up to set email alerts
|

A Polymorphism in the TC21 Promoter Associates with an Unfavorable Tamoxifen Treatment Outcome in Breast Cancer

Abstract: Tamoxifen therapy is a standard in the treatment of estrogen receptor (ER)-positive breast cancer; however, its efficacy varies widely among patients. In addition to interpatient differences in the tamoxifen-metabolizing capacity, there is growing evidence that crosstalk between ER and growth factor signaling contributes to tamoxifen resistance. We focused on TC21, a member of the Ras superfamily, to investigate the influence of the TC21 À582C>T promoter polymorphism on TC21 expression and treatment outcome. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Specifically, high RRAS2 protein expression in breast tumor biopsies has been shown to correlate with a shorter time to relapse in tamoxifentreated patients, as does possession of a RRAS2 allele carrying the −582C→T RRAS2 promoter polymorphism present in ≈34% of European Caucasians (36). Our functional data support the case for RRAS2 playing a critical role in determining the response to tamoxifen and strengthens the argument for examining the functional effects of RRAS2 polymorphisms and how these relate to clinical outcome.…”
Section: Discussionsupporting
confidence: 76%
“…Specifically, high RRAS2 protein expression in breast tumor biopsies has been shown to correlate with a shorter time to relapse in tamoxifentreated patients, as does possession of a RRAS2 allele carrying the −582C→T RRAS2 promoter polymorphism present in ≈34% of European Caucasians (36). Our functional data support the case for RRAS2 playing a critical role in determining the response to tamoxifen and strengthens the argument for examining the functional effects of RRAS2 polymorphisms and how these relate to clinical outcome.…”
Section: Discussionsupporting
confidence: 76%
“…The sample dropout rate in this investigation was Ͻ10% across all assays, which indicates that the automated extraction method provides genomic DNA of a quality comparable to that in similar studies in which archived FFPE tissue samples were used with manual DNA extraction procedures (5 ). We selected 5 genes known to harbor germline polymorphisms that have been reported to be related to breast cancer risk or disease progression (14,15 ), to functionally influence estrogen-receptor activity (NCOA3), or to be predictive for breast cancer tamoxifen outcome (16 ). Although our data showed very high concordance rates of genotypes between tumor and corresponding normal tissue, a few samples (1.1%) showed discordant alleles between paired samples.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, the analysis of Rras2 À / À mice has revealed that this GTPase plays proactive roles during mammary gland development 18 . Furthermore, recent observations have indicated that R-RAS2 could contribute to tamoxifen resistance 19,20 , thus suggesting that the inactivation of this pathway could be beneficial for patients with oestrogen receptor-positive breast tumours. It should be noted, however, that the systemic loss of R-Ras2 leads to unexpected protumorigenic effects in the case of mouse neurofibroma 21 that, if reproduced in other cancer types and in humans, may limit the interest of anti-R-Ras2-based therapies.…”
mentioning
confidence: 99%